Advances in Energy and Power Systems Select Proceedings of ICAEDC 2017 (Lecture Notes in Electrical Engineering,, 2018)
This book comprises select proceedings of the International Conference on Advancement in Energy, Drives, and Control. It covers pioneering topics in the field of renewable energy and power management, including energy storage, distribution, and control. It also discusses methods of optimizing power distribution and generation systems. This book is of use to researchers, professionals, and students from across engineering disciplines.